Implementation of RTE and Status of KGBVs in Gujarat - Awasthi, Kashyapi (JOURNAL OF INDIAN EDUCATION, 2016)
The paper discusses the status of KGBVs in Gujarat vis-à-vis the norms and standards specified in RTE for minimum infrastructure, appointment of teachers, teacher qualification and training, pupil–teacher ratio, academic responsibility, community participation and quality interventions. The paper is an outcome of the research undertaken to study the Impact of KGBVs on Girls Education and Retention and exhausts all the 86 KGBVs spread across 19 districts (as in 2012) in Gujarat under the management of both SSA and Mahila Samakhya (MS). The tools for data collection included information schedule, check-list, observation schedule, questionnaire and unstructured interview with the school heads, teachers and members of the community, the CRCC, BRCC and Gender coordinator in district as well as state. The findings of the study reflect a mixed picture of the status of KGBVs vis-à-vis the fulfilment of norms and standards under RTE. Regarding the “retention”, it was observed that success has been achieved in bringing the girls to KGBVs with the consent of their parents. However, the promise to quality education which was the underlying focus of the KGBV scheme is still a matter of serious concern. KGBVs have a greater purpose, much beyond good food, clothes, play and a safe stay; this needs to be clear both to the functionaries as also the beneficiaries.